Ginkgetin Blocks Constitutive STAT3 Activation and Induces Apoptosis through Induction of SHP‐1 and PTEN Tyrosine Phosphatases. (12th January 2016) - Baek, Seung Ho; Lee, Jae Hwi; Ko, Jeong‐Hyeon; Lee, Hanwool; Nam, Dongwoo; Lee, Seok Geun; Yang, Woong Mo; Um, Jae‐Young; Lee, Junhee; Kim, Sung‐Hoon; Shim, Bum Sang; Ahn, Kwang Seok
Abstract : Ginkgetin, a biflavone from Ginkgo biloba leaves, is known to exhibit antiinflammatory, antifungal, neuroprotective, and antitumor activities, but its precise mechanism of action has not been fully elucidated. Because the aberrant activation of STAT3 has been linked with regulation of inflammation, proliferation, invasion, and metastasis of tumors, we hypothesized that ginkgetin modulates the activation of STAT3 in tumor cells. We found that ginkgetin clearly suppressed constitutive phosphorylation of STAT3 through inhibition of the activation of upstream JAK1 and c‐Src kinases and nuclear translocation of STAT3 on both A549 and FaDu cells. Treatment with sodium pervanadate reversed the ginkgetin‐induced down‐modulation of STAT3, thereby indicating a critical role for a PTP. We also found that ginkgetin strongly induced the expression of the SHP‐1 and PTEN proteins and its mRNAs. Further, deletion of SHP‐1 and PTEN genes by siRNA suppressed the induction of SHP‐1 and PTEN, and reversed the inhibition of STAT3 activation. Ginkgetin induced apoptosis as characterized by an increased accumulation of cells in subG1 phase, positive Annexin V binding, loss of mitochondrial membrane potential, down‐regulation of STAT3‐regulated gene products, and cleavage of PARP. Overall, ginkgetin abrogates STAT3 signaling pathway through induction of SHP‐1 and PTEN proteins, thus attenuating STAT3 phosphorylation and tumorigenesis. Copyright © 2016 John Wiley & Sons, Ltd.